Heart Failure Due to Mitral Stenosis Complicated Atrial Fibrillation in Pregnancy - Deddy Khairul (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. This case report aims to discuss the management of heart failure due to mitral stenosis with complications of atrial fibrillation in pregnancy. Case presentations. A 35-year-old pregnant woman came to the ER M. Djamil Hospital with complaints of shortness of breath 3 days before being admitted to the hospital. Complaints of shortness of breath accompanied by palpitations felt fast and irregular, appeared suddenly when the patient was resting, and lasted continuously. Physical examination showed a pulse rate of 120-130x/minute, increased jugular venous pressure, and palpable cardiac ictus 1 finger lateral to the left midclavicular at the V intercostal space. ECG examination revealed atrial fibrillation- rapid ventricular response (AF RVR). The patient was diagnosed with atrial fibrillation- rapid ventricular response et causa suspect mitral stenosis NYHA Fc III, et causa rheumatic heart disease. Conclusion. The management of atrial fibrillation rapid ventricular response in this patient was done by giving digoxin 0.25 mg orally. Patients are given anticoagulants to prevent thromboembolic complications. This patient was advised to undergo valve replacement surgery considering the degree of stenosis, complications, and a thorough assessment.